2012
DOI: 10.4103/0253-7613.93863
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of adverse drug reactions to artemisinin-based combination therapy in a tertiary care hospital in India

Abstract: Objectives:Antimalarial drugs are commonly prescribed for the treatment of malaria and suspected cases of malaria in India. The recent trend is to prescribe ACT and the incidence of adverse reactions to this therapy is notwell-documented in Indian population. Therefore, this study was designed to assess ADR pattern of antimalarial drugs particularly ACT in India.Materials and Methods:Over a period of 1 year, 500 patients who were administered antimalarial drugs were enrolled in the study. The World Health Orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
2
1
Order By: Relevance
“…This supports findings from China, Thailand, South East Asia and other African countries where ACTs have been used extensively and were found to be relatively safe and well tolerated . This is also in line with the prospective study of Belhekar et al who suggested that ADRs from ACTs were of moderate intensity with the ADRs most commonly reported when chloroquine was prescribed as concomitant drug. However, this study reveals that there is no statistically significant association between the use of suspect drugs and concomitant drugs in ADRs occurrence.…”
Section: Discussionsupporting
confidence: 90%
“…This supports findings from China, Thailand, South East Asia and other African countries where ACTs have been used extensively and were found to be relatively safe and well tolerated . This is also in line with the prospective study of Belhekar et al who suggested that ADRs from ACTs were of moderate intensity with the ADRs most commonly reported when chloroquine was prescribed as concomitant drug. However, this study reveals that there is no statistically significant association between the use of suspect drugs and concomitant drugs in ADRs occurrence.…”
Section: Discussionsupporting
confidence: 90%
“…This is contrary to the findings of Belhekar [29] In the opinion of this paper, self-co-administration of analgesics and hematinics may indicate patient's anticipation of some sort of pain and "weakening of blood" which needs strengthening with hematinic. Another key finding is the influence of premedication fatty meal on ADR.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, treatment with the fruit juice signi cantly increased (p 0.05) the PCV to a mean value comparable to the standard drug group. In clinical treatment of malaria infection particularly in pregnant women, blood tonics are usually prescribed in addition to the antimalarial drug [19,[70][71][72]. This is to replenish the lost RBC due to malaria infection whereas the critical antimalarial component clears the parasites.…”
Section: Discussionmentioning
confidence: 99%